Pentecostals, proselytization, and anti-Christian violence in contemporary India - Bauman, Chad M (New York : Oxford University Press, 2015)
In contemporary violence against India's Christians, Pentecostals are disproportionately targeted. Based on extensive interviews and ethnographic work, this volume accounts for this disproportionate targeting through a detailed analysis of Indian Christian history, contemporary Indian politics, and Indian social and cultural characteristics
Who are India's pentecostals? : history, definitions, deliberations -- Pentecostalism in the context of Indian history and politics -- Where the spirit (of violence) leads : the disproportionate targeting of Indian Pentecostals -- Force, fraud, and inducement? : recuperative conversions and the growth of Indian Christianity -- Missions and the Pentecostalization of Indian Christianity
Includes bibliographical references and index
Keywords: Pentecostalism -- India -- History; Pentecostals -- Violence against -- India -- History; Christians -- Violence against -- India -- History; India -- Church history